HUBUNGAN MOTIVASI DAN MASA KERJA DENGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA BAGIAN PENGGILINGAN KARET DI PT. PERINDUSTRIAN DAN PERDAGANGAN BANGKINANG - Rofi Mazdani Mazdani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
Data on work accident cases in Indonesia is also high, according to the Republic of Indonesia Employment BPJS in 2017, that from 2015 to 2017 the highest accident rate in 2017 was 36.78. The purpose of this study was to determine the relationship of motivation and years of service with the use of Personal Protective Equipment (PPE) in PT. Bangkinang Industry and Trade 2018. The design of this study uses quantitative analytic with cross sectional. The population of this research is all employees who work in the rubber grinding section at PT. Industry and Trade in 2018, a total of 46 people in total. The sample used in this study was a total sampling of 46 people who worked in the rubber grinding section. Data analysis was performed univariately and bivariately using the chi-square test. The results of this study indicate that there is a significant relationship between motivation and personal protective equipment (PPE) designated with p value (0.004) â‰¤ Î± (0.05). The results of this study indicate that there is a significant relationship between tenure and the use of personal protective equipment (PPE) designated with p value (0.012) ï‚£ ï¡ (0.05). It is expected that PT. Bangkinang Industry and Trade, can be taken into consideration in developing policies and strategies related to the issue of the use of personal protective equipment in order to carry out counseling about the importance of using personal protective equipment.